Effects of eurycoma longifolia jack supplementation on recreational athletes' endurance running performance and physiological responses in the heat - Ayu Suzailiana, Muhamad (2009)
This study investigated the effects of Eurycoma longifolia Jack supplementation on recreational athletes' endurance running performance and physiological responses in the heat. Nine healthy male recreational athletes (Age: 23.3 ± 4.3 years old; Body weight: 69.2 ± 9.6 kg; V02max: 43.1 ± 6.6 ml.kg-1.min-1) were recruited for this study. In this double blind, placebo-controlled cross-over study, subjects completed 2 endurance running trials, performed on separate days, after either Eurycoma Jongifolia Jack (75 mg of Eurycoma longifolia Jack per capsule) or placebo supplementation. Two capsules per day of either Eurycoma longifolia Jack or placebo were taken for 7 days before and one hour prior to the experimental trial. On the trial day, after 5 minutes warm-up at 50% V02max. subjects were requested to run at 60% V02max for 60 minutes. This was immediately followed by a 20 minutes time trial for determining endurance running performance. The experimental trials were carried out in the laboratory where the temperature and relative humidity were kept at approximately 31 oc and 70% respectively. Blood samples were taken before warm-up, after warm-up, and every 20 minutes during the trial to determine haemoglobin concentration, haematocrit level, and plasma glucose concentration. At every 20 minutes during the trial, 3 ml.kg-1 body weight of cool water was given to the subjects. Study results showed that endurance running performance was not different statistically (p=0.139) between Eurycoma longifolia Jack (EL) and placebo (P) trials. Similarly, oxygen uptake, heart rate, rate of perceived exertion, body weight changes, tympanic temperature, mean skin temperature, haemoglobin concentration, haematocrit level, and plasma glucose concentration were not statistically different between trials. Thus, these findings indicated that chronic supplementation of Eurycoma longifo/ia Jack with a dosage of 150 mg.day-1 for 7 days did not elicit beneficial effects on endurance running performance and physiological responses of recreational athletes in the heat.